South African medicinal plant extracts active against influenza A virus - Parvaneh Mehrbod; Muna A. Abdalla; Emmanuel M. Njoya; Aroke S. Ahmed; Fatemeh Fotouhi; Behrokh Farahmand; Dorcas A. Gado; Mansoureh Tabatabaian; Olubunmi G. Fasanmi; Jacobus N. Eloff; Lyndy J. McGaw; Folorunso O. Fasina (BMC, 2018)
Abstract Background Influenza infection remains a major health threat for animals and humans which crucially requires effective antiviral remedies. The usage of herbal medications as readily available alternatives for their compatibility with the body and fewer side effects compared to synthetic chemical treatments has become popular globally. The aim of this study was to investigate and screen in vitro anti-influenza activity of extracts of five South African medicinal plants, namely Tabernaemontana ventricosa, Cussonia spicata, Rapanea melanophloeos, Pittosporum viridiflorum and Clerodendrum glabrum, species which are used traditionally for the treatment of several diseases such as inflammatory and respiratory diseases. Methods Methanol, ethanol (100% and 30%), acetone, hot and cold water extracts of the powdered plants leaves were obtained by standard methods. The cytotoxicity was determined by the MTT colorimetric assay on MDCK cells. The concentrations below CC50 values were tested for antiviral activity against influenza A virus (IAV) in different combination treatments. The effect of extracts on viral surface glycoproteins and viral titer were tested by HI and HA virological assays, respectively. Results Based on the applied methods, the most effective results against IAV were obtained from Rapanea melanophloeos methanol leaf extract (EC50 = 113.3 μg/ml) and Pittosporum viridiflorum methanol, 100% and 30% ethanol and acetone leaf extracts (EC50 values = 3.6, 3.4, 19.2, 82.3 μg/ml, respectively) in all types of combined treatments especially in pre- and post-penetration combined treatments with highly significant effects against viral titer (P ≤ 0.01). Conclusion The outcomes offer for the first time a scientific basis for the use of extracts of Rapanea melanophloeos and Pittosporum viridiflorum against IAV. It is worth focusing on the isolation and identification of effective active compounds and elucidating the mechanism of action from these species. However, Tabernaemontana ventricosa, Cussonia spicata and Clerodendrum glabrum leaf extracts were ineffective in vitro in this study.